Produktiwiteitsmeting : 'n oorsig en toepassing - Theron, Hendrik C. B.(Hendrik Christoffel Barnard) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Ing.) -- Universiteit van Stellenbosch, 1989.